Adolescent Drinking Risks Associated with Specific Drinking Contexts. (24th July 2015) - Mair, Christina; Lipperman‐Kreda, Sharon; Gruenewald, Paul J.; Bersamin, Melina; Grube, Joel W.
<x xml:space="preserve">Abstract</x> Background To identify drinking contexts toward which prevention efforts should be directed, associations of context‐specific alcohol use (past‐year frequency of drinking and heavier drinking in the context) with a range of alcohol‐related problems were examined in a population sample of adolescents. Methods A sample of youths (ages 15 to 18) residing in 50 medium‐to‐large California cities (n = 473 drinkers) was obtained. Respondents provided information about 7 past‐year alcohol‐related problems in 3 domains (physiological consequences, alcohol‐related violence, and conflict/trouble) and the number of times in the past year they used 6 distinct drinking contexts (parties, restaurants/bars, parking lots/street corners, beaches/parks, respondent's home without parents, and someone else's home without parents). Context‐specific dose–response model was estimated for each context using censored Tobit models with heteroskedasticity corrections. Results Physiological problems were associated with more frequent drinking in 5 of 6 contexts. Heavier drinking in restaurants/bars/nightclubs (b = 0.22, SE = 0.10) and someone else's home without parents (b = 0.14, SE = 0.06) was associated with greater risk of violence. Conflict/trouble was associated with more frequent drinking in parking lots/street corners, declining at higher levels of drinking. Conclusions Certain drinking contexts are related to problems among youths, some because they are associated with frequent alcohol consumption and others because they are associated with heavier drinking. Identifying which drinking contexts are related to specific alcohol‐related problems and why is an essential component of developing effective preventive interventions.